Ambulance Utilization in New York City after the Implementation of the Affordable Care Act - Charles Courtemanche; Andrew I. Friedson; Daniel I. Rees (Institute of Labor Economics (IZA), 2018)
Expanding insurance coverage could, by insulating patients from having to pay full cost, encourage the utilization of arguably unnecessary medical services. It could also eliminate (or at least diminish) the need for emergency services through increasing access to preventive care. Using publicly available data from New York City for the period 2013-2016, we explore the effect of the Affordable Care Act (ACA) on the volume and composition of ambulance dispatches. Consistent with the argument that expanding insurance coverage encourages the utilization of unnecessary medical services, we find that, as compared to dispatches for more severe injuries, dispatches for minor injuries rose sharply after the implementation of the ACA. By contrast, dispatches for pre-labor pregnancy complications decreased as compared to dispatches for women in labor.
Keywords: I11; I13; I18; 330; Affordable Care Act; ambulance; emergency medical service; health insurance; moral hazard